A Raman technique applicable for the analysis of the working principle of promoters and inhibitors of gas hydrate formation - Will, Stefan; Bräuer, Andreas; Hankel, Robert; Mehnert, Markus; Schuster, Julian (Journal of Raman Spectroscopy, 2015)
We report a Raman technique applicable for the in situ analysis of the development of hydrogen bonds in the liquid water-rich phase just before the onset of gas hydrate formation. Herewith, the phase transition as well as the working principle of hydrate formation inhibitors and promoters can be analyzed. (C) 2015 The Authors. Journal of Raman Spectroscopy published by John Wiley & Sons Ltd.
Keywords: gas hydrate; inhibitor; Raman spectroscopy; hydrogen bond; OH stretch vibration